2007
DOI: 10.1002/joc.1551
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal forecasting of East Asian summer monsoon based on oceanic heat sources

Abstract: We use the upper-level divergence zone at 150 hPa to define the areas of study for the East Asian summer monsoon (EASM) and to show the advances and retreats of the EASM. We find that the EASM can be subdivided into a northern and southern component with distinctly different driving mechanisms. The northern EASM (NEASM) is affected by heat sources in the tropical oceans related to El Niño events while the southern EASM (SEASM) is affected by the subtropical oceans related to a North Pacific sea surface tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Yang and Lau (2004) found that the interannual variation of the summer precipitation over central eastern China and over southern coastal China is correlated with a north-south dipole mode of SST anomalies over the western North Pacific, the tropical Indian Ocean and the warm pool: when SSTs are abnormally warm over the warm pool and northern Indian Ocean and are abnormally cold over the western North Pacific, summer precipitation tends to be heavier than usual in central eastern China but to be less in southern coastal China. Lee et al (2008) found that the north EASM precipitation is negatively correlated with the tropical western Pacific SST and is positively correlated to the tropical Indian Ocean SST, and that the south EASM precipitation is positively correlated with the western North Pacific SST but has no obvious correlation with the Indian Ocean SST. However, also based on observational data, Saji and Yamagata (2003) found that the precipitation over India and southern China is enhanced during the positive IOD (Indian Ocean dipole) event, an event which is characterized by anomalous cooling in the eastern equatorial Indian Ocean and anomalous warming in the western equatorial Indian Ocean.…”
Section: Pure Contribution Of the Ipwp Sst On The Easmmentioning
confidence: 95%
“…Yang and Lau (2004) found that the interannual variation of the summer precipitation over central eastern China and over southern coastal China is correlated with a north-south dipole mode of SST anomalies over the western North Pacific, the tropical Indian Ocean and the warm pool: when SSTs are abnormally warm over the warm pool and northern Indian Ocean and are abnormally cold over the western North Pacific, summer precipitation tends to be heavier than usual in central eastern China but to be less in southern coastal China. Lee et al (2008) found that the north EASM precipitation is negatively correlated with the tropical western Pacific SST and is positively correlated to the tropical Indian Ocean SST, and that the south EASM precipitation is positively correlated with the western North Pacific SST but has no obvious correlation with the Indian Ocean SST. However, also based on observational data, Saji and Yamagata (2003) found that the precipitation over India and southern China is enhanced during the positive IOD (Indian Ocean dipole) event, an event which is characterized by anomalous cooling in the eastern equatorial Indian Ocean and anomalous warming in the western equatorial Indian Ocean.…”
Section: Pure Contribution Of the Ipwp Sst On The Easmmentioning
confidence: 95%
“…Significant regions at the 90 and 95% levels are contoured. The relationship between NEASM precipitation and El Niño during the premonsoon season (December through May) is examined using a statistical forecast model of Lee et al [2008] (). where “SST in the TEP” is SST in the tropical eastern Pacific (5°S∼5°N, 170°W∼80°W), “SST in the TWP” is SST in the tropical western Pacific (0°∼15°N, 130°E∼160°E), “SST in the TIO” is SST in the tropical Indian Ocean (10°S∼10°N, 40°∼100°E), and “OHC in the TIO” is ocean heat content in the tropical Indian Ocean (20°S∼15°N, 50°E∼70°E) during the premonsoon season.…”
Section: Methods and Datamentioning
confidence: 99%
“…In order to elucidate the physical mechanisms between the NEASM and El Niño shown in the observational analysis [ Lee et al , 2008], we examine mean JJA differences in 850 hPa wind vector and vorticity between the El Niño and control simulations (Figure 5, left). For the El Niño run (i.e., warm SST anomalies in the tropical eastern Pacific), there are cold SST anomalies in the tropical western Pacific, WNP, and western South Pacific (a horseshoe pattern (see Figure 1)).…”
Section: El Niño Sensitivity Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, SSTdifferenced dipoles provide stronger correlation with summer rainfall over the Loess Plateau as compared to consideration of just positive or negative SSTs (Yasuda et al, 2009). Links to the summer monsoon rainfall (JJA) of East Asia (20°-50° N, 110°-145° E) with dipoles over the Pacific Ocean at 6-month time lag (DJF) were reported by Lee et al (2008). We also selected significant dipoles to maximize the correlation and predictive ability of the relationships between SST and summer rainfall.…”
Section: Sst Dipole Differencementioning
confidence: 99%